The safety concerns regarding immune checkpoint inhibitors in liver cancer patients rising mainly from CHB - Shike Lou; Zhujun Cao; Wanqing Chi; Xiaoyin Wang; Mingyang Feng; Lanyi Lin; Yezhou Ding; Kehui Liu; Lihong Qu; Gangde Zhao; Shisan Bao; Hui Wang (Frontiers Media S.A., 2023)
Aim: To analyze the safety of immune checkpoint inhibitors in primary liver cancer patients and to identify the risk factors for immune-related adverse events (irAEs).Methods: The study enrolled 106 patients with primary liver cancer, including 81 with hepatocellular carcinoma and 25 with intrahepatic cholangiocarcinoma. We analyzed the differences between groups in irAE occurrence, including those with and without targeted drugs and those who received interventional therapy.Results: The incidence of irAEs was 39%, with thyroid function, liver function, and skin events being the most common. There was no correlation among irAE incidence and the liver cancer type, stage, or severity; grade of Child-Pugh score; and Barcelona Clinical Liver Cancer classification. However, being overweight was a significant risk factor for irAEs, correlating with high body mass index. The combination of targeted drugs and/or transcatheter arterial chemoembolization therapy did not increase the incidence of irAEs.Conclusion: Being overweight is a potential risk factor for irAEs in primary liver cancer patients. However, there is no correlation between irAE incidence and the liver cancer type, stage, or severity or a combination of targeted drugs or transarterial chemoembolization therapy.